Analysis of Pulsed Laser Target Echo Characteristics in Non-Uniform Smoke Environments - Chenyoushi Xu; Ruihua Zhang; Zhen Zheng; Bingting Zha; Weiping Cao; He Zhang (Photonics)
This study establishes a mathematical model for analyzing pulsed laser target echo signals in non-uniform smoke environments, thereby enabling evaluations of the target echo characteristics of laser detection systems under various smoke conditions. A semi-analytical Monte Carlo method for laser reception is developed by integrating the T-matrix scattering phase function rejection method with the characteristics of the non-uniform smoke environment. The effects of the pulse width, smoke concentration, target reflectance, and target distance on the laser echo signal waveform are studied in detail. The results indicate that when the pulse width is small (τ = 5 ns), the echo signal exhibits a dual-peak profile due to the signals from the backscattered smoke particles and the target echo. Moreover, the smoke concentration significantly affects the amplitude of the backscatter signal. When the pulse width is large (τ ≥ 40 ns), the echo signal peak is a combination of both signals, where the amplitude increases with increasing pulse width but decreases with the increasing smoke concentration. Additionally, the target echo signal amplitude is positively correlated with the target reflectance and negatively correlated with the target distance. The accuracy of the proposed model is verified by comparing the simulation results with the experimental data. Overall, this study provides a theoretical foundation for target identification and detection in smoky environments for laser fuze applications and the analysis of laser detection characteristics in smoky environments.